Monitoring of mangroves changes in Pulau Kukup using geographical information system (GIS) - Nordin, Nur Hazimah; Abdul Rahman, Ainul Husna; Abdul Wahab, Norshahriah; Tengku Sembok, Tengku Mohd; Mohd Shukran, Mohd Afizi; Mohd Yunus, Mohd Sidek Fadhil; Isnan, Sarah; Abdul Shukur, Mohamad Rushd 'Afif 'Abda (2022)
Mangroves forests provide a support to the coastal livelihood, ecosystem, socioeconomic and also the environment. In Malaysia, the mangroves forest has been in declining rate causes by a few factor such as conversion to shrimps ponds, urban development and tourism. Such threats led to increasing demand for detailed mangrove maps for the purpose of measuring the extent of deterioration of the mangrove ecosystem. However, it is difficult to produce a detailed mangrove map mainly because mangrove forest is very difficult to access. Remote sensing technology provides a genuine alternative to the traditional field-based method of mangrove mapping and monitoring. This study analyses and map the mangrove forest changes at Pulau Kukup, Ramsar Site Johor from 2013 until 2021 using the Normalized Difference Vegetation Index (NDVI). The findings of this study are the mangrove forests in Pulau Kukup, Ramsar Site Johor, revealed an unfavourable shift leading to deforestation from 2013 to 2016. However, between 2019 and 2021, the mangrove forest improves as the forest's vegetation grows.